Perceived Effects of Electronic Filing and Billing Systems for Lecturers as Researchers - Juli Ratnawati; Nataliastyo Tah (Universitas Islam Sultan Agung (UNISSULA), Faculty of Economics, Department of Accounting, 2021)
Tax is the main source of government revenue so that the government strives to make taxpayers more obedient in carrying out their obligations. The provision of information technology is a breakthrough made by the government to improve taxpayer compliance. The purpose of this study is to analyze the use of e-filing and e-billing applications for tax compliance and the understanding of lecturers in their role as researchers and taxpayers. The study used the theories of Technology Acceptance Model (TAM) and Theory of Reasoned Action (TRA) for explaining the correlation between variables used. The sampling technique used purposive sampling, and the respondents in this study were 123 lecturers as researchers in Semarang City who used the e-filing system in their tax reporting and understood the use of the e-billing system as a tax payment application. The analysis technique used was multiple regression analysis. The results of the study showed that the use of e-filing and e-billing actually affects the researchers' tax compliance.Keywords: compliance, e-billing, e-filing, system, taxABSTRAKPajak adalah sumber utama pendapatan pemerintah sehingga pemerintah berupaya membuat pembayar pajak lebih patuh dalam menjalankan kewajibannya. Penyediaan teknologi informasi merupakan terobosan yang dilakukan oleh pemerintah untuk meningkatkan kepatuhan wajib pajak. Tujuan dari penelitian ini adalah untuk menganalisis penggunaan aplikasi e-filing dan e-billing untuk kepatuhan pajak dan pemahaman dosen dalam perannya sebagai peneliti dan juga sebagai pembayar pajak. Penelitian ini menggunakan teori Technology Acceptance Model (TAM) dan Theory of Reasoned Action (TRA) untuk menjelaskan korelasi antara variabel yang digunakan. Teknik pengambilan sampel menggunakan purposive sampling, dan responden dalam penelitian ini adalah 123 dosen sebagai peneliti di Kota Semarang yang menggunakan sistem e-filing dalam pelaporan pajak mereka dan memahami penggunaan sistem e-billing sebagai aplikasi pembayaran pajak. Teknik analisis yang digunakan adalah analisis regresi berganda. Hasil penelitian menunjukkan bahwa penggunaan e-filing dan e-billing mampu mempengaruhi kepatuhan pajak para dosen sebagai peneliti.Kata kunci: kepatuhan, e-billing, e-filing, sistem; pajak